2018
DOI: 10.1097/md.0000000000011143
|View full text |Cite
|
Sign up to set email alerts
|

Sustained clinical response after single course of rituximab as first-line monotherapy in adult-onset asthma and periocular xanthogranulomas syndrome associated with IgG4-related disease

Abstract: Rationale:IgG4-related disease (IgG4-RD) is an emerging immune-mediated disease characterized by multi-organ involvement and variable clinical behavior.Patient concerns:We describe the case of a 50-year-old woman affected by a rare variant of IgG4-RD, characterized by eyelid xanthelasmas, adult-onset asthma and salivary and lacrimal glands enlargement. Multiple lymphadenopathies and a pulmonary mass were present at initial evaluation.Inteventions:After a single course of rituximab (2g in 2 refracted doses), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Some studies have shown that the performance of tracheostomy early than later aids in easier nursing care, weaning and decreases the incidence of ventilator associated pneumonia. 29 However, the TracMan trial did not show any advantage of early (≤ 4 days) tracheostomy in terms of improvement in 30-day mortality and other important secondary outcomes. 30 Other studies indicated that the only advantage of an early tracheostomy to a later tracheostomy was the earlier weaning times.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies have shown that the performance of tracheostomy early than later aids in easier nursing care, weaning and decreases the incidence of ventilator associated pneumonia. 29 However, the TracMan trial did not show any advantage of early (≤ 4 days) tracheostomy in terms of improvement in 30-day mortality and other important secondary outcomes. 30 Other studies indicated that the only advantage of an early tracheostomy to a later tracheostomy was the earlier weaning times.…”
Section: Discussionmentioning
confidence: 92%
“…30 Other studies indicated that the only advantage of an early tracheostomy to a later tracheostomy was the earlier weaning times. 29 In our hospital's setup, patient turnover and demand for ICU is very high. It is because of this reason that earlier weaning from mechanical ventilation is an important goal.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 6 , 8 , 10 , 12 , 26 The addition of other immunosuppressive agents, such as cyclophosphamide and cyclosporin, have also shown efficacy in patients with this disease, 1 , 30 and it has been suggested that their respective B cell and T cell suppressive effects could be used to tailor treatments based on histopathological lymphocyte characteristics. 1 Rituximab has also shown to have a durable response in patients with AAPOX due to the likely B cell driven pathogenesis 14 , 31 , 32 though it remains unclear whether histological evidence of strongly positive CD20 + lymphocytes is necessary for successful treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Это послужило основанием для разработки новых подходов к фармакотерапии IgG4-СЗ, в том числе связанных с подавлением патологической активации В-клеток, играющих фундаментальныю роль в иммунопатогенезе заболевания [288]. Эффективность РТМ при IgG4-СЗ (около 90%) продемонстрирована в серии клини-ческих наблюдений [289][290][291][292][293][294][295][296][297][298][299][300][301], материалах национальных регистров [302,303] и открытом неконтролируемом исследовании [304]. Результаты применения РТМ при IgG4-СЗ подробно обсуждены в нашем обзоре [284].…”
Section: Igg4-связанное заболевание (Igg4-сз)unclassified